PENGEMBANGAN SLIDES AND LADDERS GAME BANGUN DATAR PERSEGI UNTUK MENINGKATKAN PROBLEM SOLVING SISWA SEKOLAH DASAR KELAS 5 - Audy Prudencia, Gabriella; Setiawan, Yohana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
After the pandemic, mathematics learning media has undergone significant changes in creative and innovative directions, for example board games. Media board games are one of the most attractive media options for students. This research aims to improve the problem-solving ability of grade 5 students through making Slides and Ladders learning media with square flat building material using research and development methods. Sugiyono's Research and Development method has 7 stages, namely: 1) Potential and problems; 2) Collection of information; 3) Product design; 4) Design validation; 5) Design improvement; 6) Product trials; and 7) Product revisions. This study stated successful with a validity rate of 80.61%, a practicality rate of 87.1% and increased effectiveness. It can be seen from the students look enthusiastic and focused judged from being able to understand the material well, understand how to play, understand the 4 stages of solving problems.